Digital linguodidactics and national identity: integrating the Abai poetic corpus into language and literature education (Eurasian Journal of Philology Science and Education, 2025)
This article explores the potential of the Abai Poetic Corpus, an open-access resource, as an effective tool for promoting national values in the modern educational process. The study consisted of two main stages: the first involved linguistic analysis based on the corpus, and the second was a pedagogical experiment conducted among senior secondary school pupils and first-year university students. At the linguistic stage, AntConc software was used to perform frequency, collocation, and concordance analyses. Several key concepts, systematically found in the works of Abai Kunanbayev, were identified: adam (a universal humanist category), aqyl (a measure of intellect and wisdom), iman (spiritual faith and moral purity), and namys (personal honor and social responsibility). These notions were shown to form the foundation of Kazakh ethical thought. At the pedagogical stage, students completed specially designed corpus-based tasks. During a three-lesson pilot experiment, it was observed that learners developed a deeper understanding of Abai’s moral triad – aqyl, qairat, zhurek (intellect, willpower, and heart) – and formed a renewed perspective on cultural heritage. Both quantitative and qualitative methods were applied, ensuring a comprehensive research approach. Furthermore, corpus-based methods helped enhance students’ skills in independent text work, data comparison, and critical thinking. The findings indicate that digital linguistic resources provide real opportunities for revitalizing national identity and enriching educational content. The results also contribute valuable insights to the field of digital linguodidactics.Keywords: Abai Kunanbayev, corpus linguistics, poetic corpus, national identity, moral education, digital pedagogy.